STUDY THE EFFECT OF PURIFIED CATECHINS OF GREEN TEA ONTHE MOST IMPORTANT CAUSES OF BACTERIAL INFECTIONS OFTHE URINARY TRACT AND SYNERGISTIC EFFECT - Al-jumaily, ESSAM; Al-Abdli, Yasir; Nasser, Nazar (Iraqi Journal of Science, 2024)
Two hundred urine samples were collected from patients infected with acute andchronic urinary tract infection, 85 bacterial isolate were isolated from these samplesand were diagnosed using biochemical tests and kit API test, most of them identifiedE.coli (23.5%) K.pneumoniae rate (17.6%). Isolates were selected E.coli andK.pneumoniae according to their isolation rate from urinary tract infection cases andtheir antibiotic resistance. The inhibition effect of the purified catechin from thegreen tea was studied when the isolates were grown in the following concentrations(25, 50,75, 100) mg/ml. The concentration of 100 mg/ml showed a high actionagainst the two species. The combination effect of the purified catechin wasestimated with both Amikacin and Gentamycin on the resistant isolates to theseantibiotics (E.coli and K.pneumoniae) and has been compared to the minimum inhibitor concentration of the isolates before and after the confusion of antioxidants,as the effect of mixing Amikacin and Gentamycin with Catechin, it gave a synergiceffect with Amikacin on two isolates, either Gentamycin gave synergic effect onK.pneumoniae.